Sandfly species diversity in association with human activities in the Kani tribe settlements of the Western Ghats, Thiruvananthapuram, Kerala, India - Srinivasan Ranganathan AND Subramanian Swaminathan (Mem Inst Oswaldo Cruz, Rio de Janeiro, 2015)
Sandfly prevalence in the Kani tribe settlements of Western Ghats in India was investigated. A total of 1,279 sandflies comprising 17 species was obtained. Sandfly abundance showed a negative correlation (r = -0.97, p = 0.003) with increase in altitudinal ranges from 0-1,000 m. When sandfly samples were grouped according to land- scape characteristics of the location, the estimated Shannon-Weiner index (H) and species richness index (S) were high and species evenness index (J) was low in settlements located at 0-300 m altitudinal range. On the contrary, the values of H and J were high, while S was low at 301-600 m altitudinal range. With further increase in altitude, species diversity, S and J were low. Though the relative abundance of sandflies decreased with increase in altitude, the influence of altitudinal variation could not be attributed to determine sandfly diversity, since the number of sampling units were not uniform at all the altitudinal gradients due to nonavailability of suitable resting shelters. Sandfly species showed great aggregation at 0-300 m altitude interval, where not only the number of settlements were maximum (n = 19), but also the environmental conditions favoured sandfly abundance due to the concentration of tribal settlements, human dwellings and his activities.